Directional drilling attitude control with input disturbances and feedback delay - Inyang, Isonguyo J.; Whidborne, James F.; Bayliss, Martin T. (Elsevier, 2017)
This paper presents a general approach for the attitude control of directional drilling tools for the oil and gas industry. It extends the recent work where a kinematic bilinear model of the directional drilling tool was developed and used as the basis for Constant Build Rate (CBR) controller design. The CBR controller in combination with a modified Smith Predictor (SP) is implemented for the attitude control of the directional drilling. The results of a transient simulation of the proposed modified SP-CBR controller are presented and compared with that from the CBR controller of the earlier studies. It is shown that the modified SP-CBR controller significantly reduces the adverse effects of input disturbances and time delay on the feedback measurements with respect to stability and performance.
Keywords: Directional Drilling; Attitude Control; Bilinear; Feedback Delay; Input Disturbances